Ultrasound-facilitated, catheter-directed thrombolysis vs anticoagulation alone for acute intermediate-high-risk pulmonary embolism: Rationale and design of the HI-PEITHO study - Klok, Frederikus A.; Piazza, Gregory; Sharp, Andrew S.P.; Ní Ainle, Fionnuala; Jaff, Michael R.; Chauhan, Nikhil; Patel, Binal; Barco, Stefano; Goldhaber, Samuel Z.; Kucher, Nils; Lang, Irene M.; Schmidtmann, Irene; et al. (The American heart journal, 2022)
Due to the bleeding risk of full-dose systemic thrombolysis and the lack of major trials focusing on the clinical benefits of catheter-directed treatment, heparin antiocoagulation remains the standard of care for patients with intermediate-high-risk pulmonary embolism (PE). The Higher-Risk Pulmonary Embolism Thrombolysis (HI-PEITHO) study (ClinicalTrials.gov Identifier: NCT04790370) is a multinational multicenter randomized controlled parallel-group comparison trial. Patients with: (1) confirmed acute PE; (2) evidence of right ventricular (RV) dysfunction on imaging; (3) a positive cardiac troponin test; and (4) clinical criteria indicating an elevated risk of early death or imminent hemodynamic collapse, will be randomized 1:1 to treatment with a standardized protocol of ultrasound-facilitated catheter-directed thrombolysis plus anticoagulation, vs anticoagulation alone. The primary outcome is a composite of PE-related mortality, cardiorespiratory decompensation or collapse, or non-fatal symptomatic and objectively confirmed PE recurrence, within 7 days of randomization. Further assessments cover, apart from bleeding complications, a broad spectrum of functional and patient-reported outcomes including quality of life indicators, functional status and the utilization of health care resources over a 12-month follow-up period. The trial plans to include 406 patients, but the adaptive design permits a sample size increase depending on the results of the predefined interim analysis. As of May 11, 2022, 27 subjects have been enrolled. The trial is funded by Boston Scientific Corporation and through collaborative research agreements with University of Mainz and The PERT Consortium. Regardless of the outcome, HI-PEITHO will establish the first-line treatment in intermediate-high risk PE patients with imminent hemodynamic collapse. The trial is expected to inform international guidelines and set the standard for evaluation of catheter-directed reperfusion options in the future.